Error Analysis and Corrective Feedback in Spanish-Portuguese-Language Interactions in Teletandem Contexts - Aponte Montejo, Consuelo (Íkala, Revista de Lenguaje y Cultura, 2019)
In applied linguistics, teaching/learning of closely-related languages has benefited from the error-analysis model (ea), based on contrastive analysis (ca) and inter-language approaches. This case study aims at analyzing the types of errors made by a Colombian university student in learning Portuguese as a foreign language (pfl), as well as the most common corrective feedback (cf) he received when interacting with a Brazilian student in an institutional-integrated-teletandem-context (ttdii, by its acronym in Portuguese), and at looking at the implications of this method in his learning process. This is an ethnographic exploratory study including the ae approach and its classification. Findings show improved linguisic competence by the student, probably as a result of reflection upon his learning process, particularly his errors, which were gradually decreasing as interactions moved forward.